MODELLING OF THE BAGULAR ANEURYSMS OF THE WALL OF THE BLOOD VESSEL TAKING INTO ACCOUNT THE RHEOLOGICAL PROPERTIES OF THE BLOOD (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The article presents some results of the modeling of the bag-like aneurysm by the finite element method. The model takes into account the specificity of the blood flow from the point of view of various rheological models, as well as a significant change in the shape of the saccular aneurysm depending on pressure.